Penanggulangan Stunting Melalui Modal Sosial di Desa Besmarak Kecamatan Nekamese Kabupaten Kupang - Nursalam N; Melkisedek N.B.C. Neolaka; William Djani; Hendrik Toda (PT.Mantaya Idea Batara, 2021)
Stunting is one of the public problems that need attention and handling. The incidence of stunting if leftunchecked can have implications for the quality of human resources, namely in addition to risking physicalgrowth barriers and children's vulnerability to disease, it also causes cognitive development barriers that will affectchildren's intelligence and productivity levels in the future. The community service (PPM) which is carried out in theform of counseling in Besmarak village, Nekamese sub-district, Kupang regency is expected to provide knowledgeto the community that solving the stunting problem is not only through health and nutrition improvementassistance provided by the government, but also through community social capital, namely through social networksand community trust norms. There is a strong relationship between social capital and solving various publicproblems, so that people with higher social capital also have higher awareness, they are able to take collectiveaction in preventing stunting.